Coronary artery bypass graft surgery versus stenting for patients with chronic kidney disease and complex coronary artery disease: a systematic review and meta-analysis. (March 2021) - Cui, Kongyong; Liu, Hong; Yuan, Fei; Xu, Feng; Zhang, Min; Zhang, Mingduo; Wang, Wei; Zhang, Dongfeng; Tian, Jinfan; Lyu, Shuzheng; Dou, Kefei
Background: The relative role of coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) with stent implantation in patients with chronic kidney disease (CKD) and complex coronary artery disease (CAD) remains debatable due to the lack of randomized controlled trials (RCTs). We therefore performed this meta-analysis to compare the outcomes of the two strategies in CKD patients with multivessel and/or left main disease. Methods: Electronic databases including PubMed, EMBASE and Cochrane Library were comprehensively searched to identify the eligible subgroup analysis of RCTs and propensity-matched registries. The primary endpoint was all-cause mortality during the longest follow-up. Results: Five subgroup analyses of RCTs and six propensity-matched registries involving 26, 441 patients were analyzed. Overall, the strategy of CABG was associated with lower risks of long-term mortality [odds ratio (OR) 0.83, 95% confidence interval (CI) 0.74–0.93], myocardial infarction (OR, 0.41; 95% CI, 0.27–0.62), and repeat revascularization (OR, 0.25; 95% CI, 0.16–0.39) compared with PCI in CKD patients with complex CAD. However, CABG was slightly associated with higher risk of stroke than PCI (OR, 1.33; 95% CI, 1.00–1.77). Nonetheless, the higher stroke risk in the CABG group no longer existed during long-term follow-up (OR, 0.92; 95% CI, 0.37–2.25) (>3 years). Conclusion: This meta-analysis supports the current guideline advising CABG for patients with CKD and complex CAD. At the expense of slightly increased risk of stroke, CABG reduces the incidences of long-term all-cause death, myocardial infarction and repeat revascularization compared with PCI.